Challenges and Implications of Virtual Reality in History Education: A Systematic Review - Villena-Taranilla, Rafael; Diago, Pascual D. (Applied Sciences, 2025)
Virtual Reality (VR) has emerged as a promising tool for history education, offering immersive and interactive learning experiences. However, its implementation in educational settings presents several challenges that remain under-explored. This systematic review, conducted using the Preferred Reporting Items for Systematic reviews and Meta-Analyses (PRISMA) methodology, aims to identify the main technical, usability, economic, psychological, social, and ethical challenges associated with the use of VR in history teaching. A literature search was performed in the Scopus (Elsevier) database, retrieving 2794 studies, from which a final selection of 14 papers was made based on predefined eligibility criteria. The findings indicate that interoperability issues, high hardware and software requirements, and navigation difficulties hinder VR integration. Moreover, usability concerns, including complex interfaces and cognitive overload, affect both students and educators, emphasizing the need for specialized teacher training. Economic barriers, such as the high cost of VR equipment and software, limit accessibility in resource-constrained institutions. Additionally, psychological and social challenges, including user discomfort, confusion between reality and fiction, and ethical concerns, were identified. These findings highlight the necessity of addressing these limitations to optimize VR’s pedagogical potential in history education. Future research should focus on developing cost-effective solutions, enhancing usability, and designing comprehensive training programs to facilitate the effective adoption of VR in educational contexts.
Keywords: virtual reality; systematic review; history education; history didactics; technology